Perancangan Website Company Profile Perusahaan CV. CUP10INDO Menggunakan Metode Design Thinking - Abdurrahman Ibnul Rasidi; Nur Ghaniaviyanto Ramadhan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
CV.CUP10INDO is a newly pioneering company in the field of export of local products. Just like other business people, CV.CUP10INDO certainly needs media to convey information both from the product to be exported and information about the company's profile. In export activities, it is certain to rely on valid information because export activities involve many parties. This is due to the lack of valid information about existing products so that there are some consumers who cancel their orders. In order for this incident not to recur, it is necessary to create a company profile website that will be very profitable for CV.CUP10INDO because information will be quickly and precisely conveyed to consumers. Researchers use the Design thinking method to design a company profile website because the thinking process of this method is human centered design which means it is centered on the user itself. After the website has been completed, it is necessary to test whether the web is feasible or not. At the web testing stage, researchers use usability testing in a moderate remote manner and use SUS as a benchmark which gets a final score of 78 and gets a good grade which means the web is acceptable